A Evolução e Consolidação das Práticas de Governança Corporativa no Banco do Brasil S.A. entre 1996 e 2006 - Paixão, Renato de Almeida Vargas (2008)
The purpose of this dissertation is to identify the main historical and institutional facts that have led to the present corporate governance policy adopted by Banco do Brasil S.A. (BB). The good practices of corporate governance aim to increase corporate value and facilitate the funding of capital and contribute to company¿s duration over the time. Besides, ensure to the shareholders some governance principles such as disclosure', 'compliance', 'accountability', 'fairness' and ¿corporate responsability¿ By the time BB has been shown its concern about disclosure especially for its close relationship with principal shareholder. ¿ the Brazilian Government, other equity partners and the Brazilian society. Banco do Brasil was founded in 1808 by the Portuguese emperor Dom João VI and today is the oldest bank operating in the local market. BB also was the first company listed on Brazilian stock exchange since 1906. In 1996, after some net losses, the Brazilian Government raised the bank¿s authorized capital in R$ 8 billion. This fact established the first attempts to develop bank¿s corporate governance through the years. Banco do Brasil currently has more than 24.4 million customers, served by a network of 15,113 points of service with R$ 296.4 billion in total assets2. The purpose of this work is to demonstrate the principal measures adopted by Banco do Brasil to reach the top level of corporate governance in the Brazilian stock exchange ¿ the New Market of Bovespa. This top position was reached in June 2006. Banco do Brasil was the first state owned company to reach this level of governance in Brazil. This dissertation was based on Yin's taxonomy methodology as a single case study. This research has used documents and file records as sources of evidence, including longitudinally research to demonstrate the evolution facts through time.'